Effects of increasing zinc from zinc sulfate or zinc hydroxychloride on finishing pig growth performance and carcass characteristics - Carpenter, C. B.; Coble, K.; Woodworth, Jason C.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S.; Usry, J. L. (My University, 2016)
A variety of zinc sources are available for use in swine trace mineral premixes. However, more research is needed to compare zinc sources and dietary levels in growing and finishing pigs in a commercial environment. A total of 1008 pigs [TR4 × (Fast Large White × L02 PIC); initially 32.1 kg BW)] were used in a 103-d growth study to determine the effects of Zn source and level on finishing pig growth performance and carcass characteristics. The 6 dietary treatments were arranged as a 2 × 3 factorial with main effects of Zn source (ZnSO4 Agrium Advance Technology, Loveland, CO or Zn Hydroxychloride; IntelliBond Z®; Micronutrients, Indianapolis, IN) or level (50, 100, or 150 ppm added Zn). There was no additional Zn provided from the trace mineral premix. There were 21 pigs per pen and 8 pens per treatment. Overall, there were no Zn source × level interactions observed for ADG or ADFI, however G:F tended (linear, P = 0.069) to be poorer when pigs were fed increasing levels of Zn from ZnSO4. Overall, there were no Zn source effects for growth performance observed. For Zn level main effects, ADG was maximized (quadratic, P = 0.007) and ending BW was heaviest (quadratic, P = 0.011) when diets contained 100 ppm of Zn. Feed efficiency was poorer (linear, P = 0.006) when pigs were fed increasing levels of Zn. For carcass characteristics, pigs fed diets with Zn Hydroxychloride had heavier (P = 0.041) HCW than those fed ZnSO4. Also carcass yield increased (linear, P = 0.027) when pigs were fed increasing levels of Zn and HCW was maximized (quadratic, P = 0.006) when diets contained 100 ppm of Zn. These results suggest that a total of 100 ppm added Zn is enough to maximize ending BW, ADG and HCW, but G:F worsened as Zn level increased. Zn source did not impact growth performance; however, pigs fed Zn Hydroxychloride had increased HCW compared to those fed ZnSO4.
Citation: Carpenter, C. B., Coble, K., Woodworth, J. C., DeRouchey, J. M., Tokach, M. D., Goodband, R. D., . . . Usry, J. L. (2016). Effects of increasing zinc from zinc sulfate or zinc hydroxychloride on finishing pig growth performance and carcass characteristics. Journal of Animal Science, 94, 141-141. doi:10.2527/msasas2016-301
Keywords: Finishing Pig; Zinc Sulfate; Zinc Hydroxychloride; Agriculture